Thermal analysis of ligand-DNA interaction: determination of binding parameters - Ekaterina Bereznyak; Natalia Gladkovskaya; Evgeniy Dukhopelnykov; Anastasiya Gerus; Anastasiya Lantushenko; Maxim Evstigneev (AIMS Biophysics, 2015)
The review discusses the methods of thermodynamic analysis of reactions of non-covalent binding of biologically active compounds with DNA, which is a key constituent of cell chromatin. Knowledge of thermodynamic profile of ligand binding with nucleic acids is important for understanding the mechanism of medico-biological action of the currently existing drugs and for designing of new drugs with improved medical effect. Thermodynamic analysis of ligand binding with DNA is based on analysis of experimentally measured changes of Gibbs free energy (ΔG), enthalpy (ΔH), entropy (ΔS) and heat capacity (ΔCр). Right selection of the methods of measurement of these parameters and understanding of limitations of currently existing approaches for numerical data analysis are crucially important for correct interpretation of the obtained results and getting insight into the mechanism of drug-DNA interaction. In the present work the currently existing methods of determination of thermodynamic parameters of ligand binding with DNA were divided into two main groups. The first group is associated with the approaches used in cases when the heating of the system does not cause melting of the biopolymer. The main focus is given to the second group of the methods which are based on description of helix-coil transition of DNA-ligand complexes with further comparison of the same transition for «free» biopolymer. The methods of computation of the binding parameters utilizing the Ising-type models and models based on the equations of chemical equilibrium are discussed.